2020
DOI: 10.12804/revistas.urosario.edu.co/apl/a.8375
|View full text |Cite
|
Sign up to set email alerts
|

Podem os pós-avisos de esclarecimento eliminar a conformidade da memória?

Abstract: Após a discussão com outra testemunha sobre um acontecimento, as pessoas podem incorporar nas suas próprias memórias informações novas e erradas e, consequentemente incluí-las em relatos posteriores ao evento. Este fenómeno apelida-se de conformidade da memória. O presente estudo teve como objetivo perceber de que forma as testemunhas podem ser protegidas desta informação falsa utilizando pós-avisos de esclarecimento. Nesta investigação utilizou-se o procedimento MORI. Inicialmente, os participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In a meta-analysis, enlightenment was the only type of warning that reduced false memories in the misinformation paradigm (Blank & Launay, 2014). Enlightenment has been previously applied to the MORI procedure, but it showed no effect (Fernandes et al, 2020): participants that were enlightened before the recognition test did not show a significant reduction of the co-witness suggestibility effect.…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations
“…In a meta-analysis, enlightenment was the only type of warning that reduced false memories in the misinformation paradigm (Blank & Launay, 2014). Enlightenment has been previously applied to the MORI procedure, but it showed no effect (Fernandes et al, 2020): participants that were enlightened before the recognition test did not show a significant reduction of the co-witness suggestibility effect.…”
Section: Methodsmentioning
confidence: 96%
“…However, there were some limitations to how enlightenment was operationalised in that research. In particular, Fernandes et al (2020) did not explicitly mention that participants saw two different videos, which may be key to understand why enlightenment did not reduce memory conformity: participants were not fully aware of the procedure and how false information was presented. In this experiment, our objective was twofold: (1) replicate Experiment 1 to further test the MORI-v procedure and (2) test an improved version of the enlightenment warning to determine whether it would protect witnesses' reports from memory distortion stemming from online discussion.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a series of studies by Paterson et al (2011), it was found that warning a witness that a co-witness may be misleading they did not prevent co-witness conformity: neither when the witness was warned a week after the discussion, nor when the witness was warned immediately after the discussion. Similarly, Fernandes et al (2020) found that extended warning (an "enlightenment') did not reduce memory conformity.…”
mentioning
confidence: 96%